CHILD L2 LEARNING OF ENGLISH IN A BILINGUAL SETTING - Fleta Guillén, Teresa (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Learning a second language (L2) in a bilingual school can be compared to first language acquisition (L1) in that both processes develop in a natural and unconscious manner. In this paper I investigate the nature of early grammars in second language acquisition. One of the main concerns is whether child learners show a developmental process in L2 acquisition and, if they do, whether there is transference from the children’s L1, and whether the L2 acquisition process resembles the L1 acquisition process. The goal of this paper is to examine the acquisition of yes-no questions, the use of explicit subjects and the omission of inflectional verbal morphology in child L2 grammars. Data come from language production corpora of children who acquire English in their early years at a bilingual school; I compare L2 learners’ data with native children’s data. Also, to find out if there are common patterns in L2 acquisition, I refer to some crosslinguistic studies carried out with child L2 learners from a variety of language backgrounds (French, Korean, Russian and Bantu languages). In order to learn more about how children approach a second language in a bilingual school, I consider input data through an art activity.